Hukum Responsif dalam Menghadapi Perubahan Sosial Sexual Cybercrimes di Tengah Kehidupan Masyarakat - Novi Enjelina Putri (Journal of Law and Administrative Science, 2024)
The development of technology and information has had a significant impact on social changes in Indonesia. Rapidly growing digitalization makes communication and mobilization easier, but on the other hand, it also opens up opportunities for crimes in cyberspace, one of which is cybercrime in the field of decency, also known as Sexual Cybercrime. This phenomenon includes acts such as the distribution of pornography, verbal sexual harassment, child exploitation, and grooming for the purpose of sexual harassment. These crimes not only cause troubling social impacts but also pose a major challenge to law enforcement. In response to this phenomenon, the Indonesian government has adopted legal tools such as the Electronic Information and Transaction Law (ITE Law) and the Pornography Law to regulate and tackle crimes that occur in cyberspace. This paper highlights the importance of responsive law in the face of social change due to technological advances. The author emphasizes that the existence of adaptive regulations is very important to protect the public from the negative impacts of technology, especially in preventing and handling Sexual Cybercrime. The research method used is normative juridical, employing statutory and case approaches. The research objective is to analyze the response of law in the face of social changes related to Sexual Cybercrime.